Look Up!: : Henrietta Leavitt, pioneering woman astronomer - Burleigh, Robert (Simon & Schuster Books for Young Readers, 2013)
An illustrated portrait of astronomer Henrietta Swan Leavitt traces the years she spent measuring stars from her position at the Harvard College Observatory and her important discoveries that enabled the scientific community to gain a fuller understanding of the universe's vast size.